Augusto Roa Bastos's Trilogy as Postmodern Practice - Helene C. Weldt-Basson (Studies in 20th & 21st Century Literature, 1998)
Augusto Roa Bastos's most recent novel, El fiscal (1993), completes the author's trilogy on the "monotheism of power," which the novel constitutes in conjunction with the prior works Hijo de hombre (1960) and Yo el Supremo (1974). These novels form a larger whole by virtue of the way in which they attempt to define Paraguay's identity through the nation's history. Hijo de hombre focuses on both the Chaco War and a series of Paraguayan civil wars; Yo el Supremo concentrates on the nineteenth-century dictatorship of Dr. José Gaspar Rodríguez de Francia; and El fiscal presents both Alfredo Stroessner's dictatorship (1954-1989) and the nineteenth-century War of the Triple Alliance (during the dictatorship of Francisco Solano López). Moreover, each novel approaches history in a way which is postmodern. This study both discusses the controversy surrounding the term "postmodernism" and analyzes the way in which these novels carry out some of the characteristics attributed to postmodernism by various critics. These postmodern traits help to unify the three novels and justify their status as a trilogy.
Keywords: Augusto Roa Bastos; El fiscal; power; Hijo de hombre; yo el supreme; novels; Paraguayan literature; Paraguayan identity; identity; hisory; Chaco War; Dr. José Gaspar Rodríguex de Francia; Alfredo Stroessner; War of the Triple Alliance; Francisco Solano López; postmodern